Predicting Lactate Threshold With Rate of Perceived Exertion in Young Competitive Male Swimmers. Issue 4 (August 2021) - da Silva, Jhonny K. F.; Sotomaior, Bruna B.; Carneiro, Carolina F.; Rodrigues, Patrick; Wharton, Lee; Osiecki, Raul
The purpose of this study was to verify the effectiveness of the rate of perceived exertion threshold (RPET) for predicting young competitive swimmers' lactate threshold (LT) during incremental testing. We enrolled 13 male athletes ( M age = 16, SD  = 0.6 years) in an incremental test protocol consisting of eight repetitions of a 100-meter crawl with 2-minute intervals between each repetition. We collected data for blood lactate concentration ([La]) and Borg scale rate of perceived exertion (RPE) at the end of each repetition. The results obtained were: M RPET = 4.98, SD = 1.12 arbitrary units (A.U.) and M lactate threshold = 4.24, SD  = 1.12 mmol.L −1, with [La] and RPE identified by the maximal deviation (Dmax) method without a significant difference ( p  > 0.05) and large correlations between DmaxLa and DmaxRPE at variables for time (r = 0.64), velocity (r = 0.67) and percentage of personal best time (PB) (r = 0.60). These results suggest that RPET is a good predictor of LT in young competitive swimmers.